2022
DOI: 10.3389/fphar.2022.923395
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Patent Medicine Shufeng Jiedu Capsules as an Adjuvant Therapy for Community-Acquired Pneumonia: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Background: Shufeng Jiedu (SFJD) capsules can be used as adjunctive treatment for patients with community-acquired pneumonia, but the effectiveness and safety of SFJD are not clear. This review aims to evaluate the effectiveness and safety of SFJD based on randomized controlled trials (RCTs).Methods: A systematic review was conducted by searching PubMed, Embase, Scopus, Web of Science, CENTRAL, CNKI, VIP, CBM, Wanfang and trial registry platforms from their inception to March 2022. Two reviewers screened studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…There was no evidence of a significant difference in adverse events between the intervention and control groups and there are no serious safety concerns ( Trill et al, 2022 ). SFJD also seems to reduce duration of symptoms in COVID-19 ( Sheng et al, 2022 ), upper respiratory tract infections ( Zhang et al, 2021 ) and in community-acquired pneumonia, when given in addition to antibiotics ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was no evidence of a significant difference in adverse events between the intervention and control groups and there are no serious safety concerns ( Trill et al, 2022 ). SFJD also seems to reduce duration of symptoms in COVID-19 ( Sheng et al, 2022 ), upper respiratory tract infections ( Zhang et al, 2021 ) and in community-acquired pneumonia, when given in addition to antibiotics ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…SFJDC has the effect of clearing heat and detoxifying, dispelling wind and relieving exterior, which has been used to treat acute upper respiratory tract infection (URI) with external wind-heat syndrome.Indicative symptoms are fever, aversion to cold, sore throat, headache, nasal congestion, runny nose and cough [1][2][3]. Clinical application studies have shown that SFJDC can also treat community-acquired pneumonia, chronic obstructive pulmonary disease(COPD), and other diseases [4][5][6][7][8]. It is recommended as the treatment guideline and recommended medication for 12 major diseases, including 'TCM Diagnosis and Treatment Protocol for Wind-warm Lung-heat Disease (Viral Pneumonia) (Mild Cases)' (2017), 'Diagnosis and Treatment Protocol for exogenous fever (URI)' (2017), and is also included in the 'National Reimbursement Drug List' and 'National Essential Medicine List' .…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese herbal medicine Shufeng Jiedu® (SFJD) capsule is a patent formula consisting of eight Chinese herbs, all of which are used traditionally for treating respiratory infections (Table 1 ). SFJD is already on the market in China for treating respiratory conditions, with promising evidence showing its effects in various acute upper RTIs [ 20 ] and community-acquired pneumonia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%